EMPOWERMENT OF MICRO ENTERPRISES IN BARITO KUALA REGENCY THROUGH THE Z-MART PROGRAM OF BAZNAS KAL-SEL - Salsabila, Eka Mutia; Dahliana, Difi; Seff, Syaugi Mubarak (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2025)
Productive Zakat or known as an Islamic philanthropic instrument that is capable of empowering and improving community welfare, such as through the Z-Mart Program by National Amil Zakat Agency (BAZNAS). However, the implications of the Z-Mart Program for Mustahik's welfare remain unknown. This study aims to reveal the implications of the Z-Mart Program in Barito Kuala Regency on mustahik welfare. Using field research method with qualitative approach. Data collection techniques include interviews, observations, and documentation. The data analysis technique uses descriptive analysis consisting of data reduction, presentation, and conclusion. This study finds that empowerment through the Z-Mart Program has a positive impact on the increase of business scale, income, skills, and welfare of mustahik. Based on these findings, it is recommended that BAZNAS continue and optimize mustahik empowerment through the Z-Mart Program.